Association between single nucleotide polymorphisms, TGF-β1 promoter methylation, and polycystic ovary syndrome - Mengge Gao; Xiaohua Liu; Heng Gu; Hang Xu; Wenyao Zhong; Xiangcai Wei; Xingming Zhong (BMC, 2024)
Abstract Background Polycystic ovarian syndrome (PCOS) is a common endocrine and metabolic disease in women. Hyperandrogenaemia (HA) and insulin resistance (IR) are the basic pathophysiological characteristics of PCOS. The aetiology of PCOS has not been fully identified and is generally believed to be related to the combined effects of genetic, metabolic, internal, and external factors. Current studies have not screened for PCOS susceptibility genes in a large population. Here, we aimed to study the effect of TGF-β1 methylation on the clinical PCOS phenotype. Methods In this study, three generations of family members with PCOS with IR as the main characteristic were selected as research subjects. Through whole exome sequencing and bioinformatic analysis, TGF-β1 was screened as the PCOS susceptibility gene in this family. The epigenetic DNA methylation level of TGF-β1 in peripheral blood was detected by heavy sulfite sequencing in patients with PCOS clinically characterised by IR, and the correlation between the DNA methylation level of the TGF-β1 gene and IR was analysed. We explored whether the degree of methylation of this gene affects IR and whether it participates in the occurrence and development of PCOS. Results The results of this study suggest that the hypomethylation of the CpG4 and CpG7 sites in the TGF-β1 gene promoter may be involved in the pathogenesis of PCOS IR by affecting the expression of the TGF-β1 gene. Conclusions This study provides new insights into the aetiology and pathogenesis of PCOS.